The Music Teaching for Development on Being Musician of Dancing Students at Guangzhou University in China - Zhe, He; Yodwised, Chutasiri; Rojanatakul, Satana (Journal of Roi Kaensarn Academi, 2023)
In 2022 the Ministry of Education made music and dance arts courses officially compulsory in primary and secondary education. Dance students always neglect the importance of music courses, and therefore learning music courses is a necessary means of accessing the primary and secondary school pathways. The purposes of this study were (1) To Study and collect Music Drama knowledge. (2) To construct Music Drama course plan. (3) To use the course for teaching experimental group. (4) To evaluate the result of teaching. This study adopts mixed research methods, qualitative and quantitative research methods. In the research stage, interviews and observations were used. the researcher observed the learning status of first-year students majoring in Dance at Guangzhou University. In the development stage, quantitative methods are adopted through experimental design and conclusions with statistical description. The 10 students in the first-year of Dance major at Guangzhou University were selected as the experimental subjects to carry out the teaching experiment Music Drama minor singing. The effect of Music Drama minor singing is analyzed through the pre-test and post-test. The researcher using the basic principles and theoretical knowledge of Music Drama combined with the author’s study and expert interviewing, after exploring and researching the academic materials available at present, aiming at the weak links of Music Drama, this paper creates the course plan for the students of Dance major. Music Drama course plan has been created, which consists of four parts: “the theoretical knowledge of Music Drama”, “Music Drama tunes singing”, “summary and review” and “final examination”. This course plan is finalized after expert interviews, aiming to explore how to teach and singing Music Drama, to improve the musical ability of developing dance students.